2013
DOI: 10.1088/0953-4075/46/11/115201
|View full text |Cite
|
Sign up to set email alerts
|

Charge-state distributions of fast diatomic carbon ions and dissociated fragments passing through microcapillaries

Abstract: We measured charge distributions of fast diatomic molecular ions after transmission through microcapillaries. Projectile beams of C2 ions with velocities of 0.89–1.79 au were incident on single-tapered capillaries with two different outlet diameters of 7.7 and 13.7 µm. We found that most of the transmitted primary C2 ions retain their incident charge states. For dissociated C1 fragments resulting from scattering with capillary-wall surfaces, their average charges increase with increasing velocity. The velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Although a realistic value of the enhancement factor may be considered to be less than 2, the work of Nebiki et al demonstrated that a tapered glass capillary can be used as a simple microbeam generator to achieve some beam density enhancement. The capillary microbeam method has since been applied to particle induced x-ray emission (PIXE), RBS (Rutherford backscattering spectrometry), and nuclear reaction analysis with various MeV-energy ions [87][88][89][90][91][92][93][94][95][96][97][98]. The RIKEN group has also started to apply capillary microbeam methods to the irradiation of intracellular organelles [99][100][101].…”
Section: Macro-size Capillariesmentioning
confidence: 99%
“…Although a realistic value of the enhancement factor may be considered to be less than 2, the work of Nebiki et al demonstrated that a tapered glass capillary can be used as a simple microbeam generator to achieve some beam density enhancement. The capillary microbeam method has since been applied to particle induced x-ray emission (PIXE), RBS (Rutherford backscattering spectrometry), and nuclear reaction analysis with various MeV-energy ions [87][88][89][90][91][92][93][94][95][96][97][98]. The RIKEN group has also started to apply capillary microbeam methods to the irradiation of intracellular organelles [99][100][101].…”
Section: Macro-size Capillariesmentioning
confidence: 99%